Gender Gap and Trade Liberalization: An Analysis of some selected SAARC countries - Audi, Marc; Ali, Amjad (Advances in Social Sciences Research Journal, 2018)
Trade liberalization plays a significant role in the development of an economy as all countries have insufficient resources and depend on trade to grow and prosper. The key objective of this study is to explore the relationship of trade liberalization on women empowerment. It also aims to find out whether it is beneficial for gender gap or not. This study utilizes the sample of five SAARC countries for the time period of 15 years, that is, from 2000 to 2014. It emphasizes on tariffs and regulatory trade barriers, which are considered significant indicators of trade liberalization, along with the freedom of trade, that is a composite index. The gender gap is measured through the female to male participation rate, whereas, gender development index(GDI) is used as a relative measure of women empowerment after adjusting HDI for gender disparity in three dimensions. The other control variable incorporated in this study includes: gross domestic product growth, education of female, female unemployment rate and the hiring regulations & minimum wage standards. The econometric technique applied is the pooled ordinary least squares (OLS) method along with various diagnostic tests. When trade liberalization goes up, it increases the GDI, meaning lower gender disparity, which in turn refers to greater women empowerment. The research concludes that whenever the trade liberalization increases, it does not reduce the gender gap, which means the female to male participation rate goes down. It encourages women to actively participate in the labor market, but it does not play a role in reducing gender gap. Education of female is essential because it creates awareness among girls and enhances their skills, which leads to empowering women, making them self-sufficient and active participants in the economic activity, which can improve their standard of living.